The Power of Reiki: Feasibility and Efficacy of Reducing Pain in Children With Cancer Undergoing Hematopoietic Stem Cell Transplantation. (September 2019) - Zucchetti, Giulia; Candela, Filippo; Bottigelli, Cristina; Campione, Gabriela; Parrinello, Annalisa; Piu, Paola; Vassallo, Elena; Fagioli, Franca
Purpose: Reiki is a growing complementary therapy in pediatric oncology that needs evidence to become more credible among the health community. A within-subject design experiment was conducted to pilot testing the feasibility and efficacy of Reiki to provide pain relief among pediatric patients undergoing hematopoietic stem cell transplantation (HSCT).Method : Pediatric patients undergoing HSCT during the inpatient phase in the Stem Cell Transplantation Unit were eligible to participate to the pilot study. Short and medium effects were assessed investigating the increase or decrease of patient's pain during three specific time periods ("delta") of the day: morning of the Reiki session versus assessment before Reiki session (within subjects control period), assessment before Reiki session versus assessment after Reiki session (within subjects experimental period) and assessment after Reiki session versus morning the day after Reiki session (within subject follow-up period). The long-term effects were verified comparing the pain evolution in the day of the Reiki session with the following rest day.Results: The effect of 88 Reiki therapy sessions in nine patients (Mage = 12; Female = 61%) was analyzed following a short, medium, and long-term perspective. Repeated-measures analysis of variance revealed a significant difference among the three periods ( F = 17, 17 p < .0001): A decrease of the pain occurred in the experimental period in short and medium term, while in the follow-up period, the pain level remained stable.Conclusions: This study demonstrates the feasibility of using Reiki therapy in pediatric cancer patients undergoing HSCT. Furthermore, these findings evidence that trained pediatric oncology nurses can insert Reiki into their clinical practice as a valid instrument for diminishing suffering from cancer in childhood.